2002
DOI: 10.1139/f02-101
|View full text |Cite
|
Sign up to set email alerts
|

Population structure of copper rockfish (Sebastes caurinus) reflects postglacial colonization and contemporary patterns of larval dispersal

Abstract: The copper rockfish (Sebastes caurinus) is a benthic, nonmigratory, rocky reef species with pelagic larval and juvenile stages lasting several months. Adults are commonly distributed in temperate coastal waters of the Pacific Ocean from British Columbia to southern California, including the inland waterways of Puget Sound, Washington, a semi-enclosed fjord system of known postglacial origin. Here, we report the distribution of genetic variation at six microsatellite DNA loci from six locations throughout the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
99
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(112 citation statements)
references
References 19 publications
11
99
2
Order By: Relevance
“…In this study, the genetic variation of wild population samples of Korean S. inermis was low relative to that reported in other Sebastes species (Rocha-Olivares et al, 2003;Buonaccorsi et al, 2002Buonaccorsi et al, , 2004, as well as other marine fishery species (DeWoody and Avise, 2000). However, similar genetic variability was reported in S. maliger (Wimberger et al, 1999) and S. thompsoni (Sekino et al, 2001).…”
Section: Discussionsupporting
confidence: 57%
“…In this study, the genetic variation of wild population samples of Korean S. inermis was low relative to that reported in other Sebastes species (Rocha-Olivares et al, 2003;Buonaccorsi et al, 2002Buonaccorsi et al, , 2004, as well as other marine fishery species (DeWoody and Avise, 2000). However, similar genetic variability was reported in S. maliger (Wimberger et al, 1999) and S. thompsoni (Sekino et al, 2001).…”
Section: Discussionsupporting
confidence: 57%
“…A very close value (mean He = 0.72 in a set of shared loci) was found among 400 grass rockfish S. rastrelliger sampled along the Pacific coasts of Oregon and California (Buonaccorsi et al, unpublished data). Buonaccorsi et al (2002) studied exactly the same loci analysed here (except for Sra7-2) in the copper rockfish Sebastes caurinus finding 0.63 ≤ He ≤ 0.71 in fish sampled throughout its geographic range. Overlapping levels of microsatellite heterozygosity (0.5-0.87) were found at six loci of the Pacific ocean perch Sebastes alutus (Miller et al, 2000).…”
Section: Genetic Diversitymentioning
confidence: 76%
“…In a study that included the same loci used here, except for Sra11-103, Buonaccorsi et al (unpublished data) also found a low and marginally significant partitioning (F ST = 0.0013, p = 0.0497) in the grass rockfish S. rastrelliger distributed continuously along the coasts of California and Oregon. The same loci, however, were all significantly differentiated (overall F ST = 0.036, p < 0.001) among populations of copper rockfish (Buonaccorsi et al, 2002).…”
Section: Population Structurementioning
confidence: 91%
See 2 more Smart Citations